EXPLORING WORKPLACE INCIVILITY AND THE ROLE OF ISLAMIC WORK ETHICS IN ACADEMIC ENVIRONMENTS - Nur Aulia Fahada Misaridin; Nur Yani Che Hussin; Raja Nurul Hafizah Raja Ismail; Nurul Khair Ishak (Journal of Islamic, Social, Economics and Development, 2023)
Workplace incivility in the academic workplace has received less attention in studies. Workplace civility in academic settings is critical for maintaining a healthy university atmosphere and boosting teaching-learning outcomes. Individuals, teams, departments, and the campus community might suffer because of workplace incivility. Therefore, academic institutions are urged to provide a civic environment. In recent years, one of the most often debated topics has been ethics, specifically Islamic work ethics (IWE) that can be applied in any business applications and behaviours. Therefore, this article will explore the fundamental concepts of Islamic work ethics as they apply to the workplace. This paper will demonstrate how Islamic work principles might improve workplace civility in an academic setting.